Neutrophil Extracellular Traps Augmented Alveolar Macrophage Pyroptosis via AIM2 Inflammasome Activation in LPS-Induced ALI/ARDS - Li H; Li Y; Song C; Hu Y; Dai M; Liu B; Pan P (Dove Medical Press, 2021)
Haitao Li,1 Yi Li,2 Chao Song,2 Yongbin Hu,3 Minhui Dai,2 Ben Liu,4 Pinhua Pan2 1First Department of Thoracic Medicine, Hunan Cancer Hospital/The Affiliated Cancer Hospital of Xiangya School of Medicine, Central South University, Changsha City, Hunan Province, People's Republic of China; 2Department of Respiratory and Critical Care Medicine, National Key Clinical Specialty, Xiangya Hospital, Central South University, Changsha City, Hunan Province, People's Republic of China; 3Department of Pathology, Xiangya Hospital, Central South University, Changsha City, Hunan Province, People's Republic of China; 4Department of Emergency, Xiangya Hospital, Central South University, Changsha City, Hunan Province, People's Republic of ChinaCorrespondence: Pinhua PanDepartment of Respiratory and Critical Care Medicine, National Key Clinical Specialty, Xiangya Hospital, Central South University, Changsha City, Hunan Province, People's Republic of ChinaEmail pinhuapan668@csu.edu.cnBackground: Uncontrollable inflammation is a critical feature of gram-negative bacterial pneumonia-induced acute respiratory distress syndrome (ARDS). Both neutrophils and alveolar macrophages participate in inflammation, but how their interaction augments inflammation and triggers ARDS is unclear. The authors hypothesize that neutrophil extracellular traps (NETs), which are formed during neutrophil NETosis, partly cause alveolar macrophage pyroptosis and worsen the severity of ARDS.Methods: The authors first analysed whether NETs and caspase-1 are involved in clinical cases of ARDS. Then, the authors employed a lipopolysaccharide (LPS)-induced ARDS model to investigate whether targeting NETs or alveolar macrophages is protective. The AIM2 sensor can bind to DNA to promote AIM2 inflammasome activation, so the authors studied whether degradation of NET DNA or silencing of the AIM2 gene could protect alveolar macrophages from pyroptosis in vitro.Results: Analysis of aspirate supernatants from ARDS patients showed that NET and caspase-1 levels were correlated with the severity of ARDS and that the levels of NETs and caspase-1 were higher in nonsurvivors than in survivors. In vivo, the NET level and proportion of pyroptotic alveolar macrophages in bronchoalveolar lavage fluid (BALF) were obviously higher in LPS-challenged mice than in control mice 24 h after injury. Administration of DNase I (a NET DNA-degrading agent) and BB-Cl-amidine (a NET formation inhibitor) alleviated alveolar macrophage pyroptosis, and Ac-YVAD-cmk (a pyroptosis inhibitor) attenuated NET levels in BALF and neutrophil infiltration in alveoli. All treatments markedly attenuated the severity of ARDS. Notably, LPS causes NETs to induce alveolar macrophage pyroptosis, and degradation of NET DNA or silencing of the AIM2 gene protected against alveolar macrophage pyroptosis.Conclusion: These findings shed light on the proinflammatory role of NETs in mediating the neutrophil-alveolar macrophage interaction, which influences the progression of ARDS.Keywords: ALI/ARDS, NETs, macrophage pyroptosis, AIM2 inflammation